Improving Students’ Ability in Speaking Using Experiential and Accelerated Learning Method - Emelia, Tengku Winona; Susanti, Susanti; Manurung, Imelda Darmayanti (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
The aim of this research is to find out an overview of the application of experiential and accelerated learning methods to improve students' speaking skills in the English subject at Brigjen Katamso Sunggal Vocational School, as well as to find out how far students' speaking skills have improved in the form of classroom action research carried out in two cycles. The speaking test is applied to find out how far students' abilities have improved in each cycle. The research results showed that there was an increase in students' speaking abilities as seen from the average pre-test score of 64.13 and post-test of 79.36. The results show that student scores increase as student success in the exam increases from 16.7% to 80%. This proves that Experential and Accelerated Learning methods can improve students' speaking skills.